Large negative tension-impedance effect in a soft ferromagnetic microwire. (13th October 2020) - Wang, Tao; Wang, Bicong; Liu, Siyuan; Luo, Yufeng; Li, Hengyu; Liu, Mei; Rao, Jinjun; Wu, Zhizheng; Pu, Huayan; Luo, Jun; Xie, Shaorong
Abstract: Large negative tension-impedance effect was found in a soft ferromagnetic FeCoNiBSiMo microwire, namely, the impedance of the microwire was greatly reduced by the presence of mechanical tensions at intermediate frequency. The impedance reductions could be attributed to the sharp declines of the cylindrical permeability induced by the mechanical tensions. High-frequency skin effect was decreased after stretching the microwire in the longitudinal direction, and the surface current of which redistributed due to the presence of mechanical tensions. A strong tension-resistance effect was found at high frequency, while a strong tension-inductance effect was found at low frequency. Significantly, the decreased skin effect in a stretched microwire is especially suitable for the development of high-frequency tension-impedance sensors requiring small impedance.